Chorangioma - A Case Report (Journal of Medicine, 2014)
We present a female patient with pregnancy associated with normal live birth and the unusual concomitance of chorangioma. It was an incidental finding during the routine microscopic examination of the placenta of the 30 year multipara whose pregnancy was clinically normal. She was admitted to the Bangladesh Medical College Hospital for labor at 34 weeks gestation. She was investigated thoroughly because of irregular pervaginal bleeding before delivary. Caesarian section was done at 37th weeks of pregnancy. The placenta was found enlarged, irregular and haemorrhagic. Histopathological examination from the sections of specimen was done and diagnosed as Chorangioma. The case is presented as below.DOI: http://dx.doi.org/10.3329/jom.v14i2.19671 J Medicine 2013, 14(2): 185-186